A shoot endosymbiont colonizes pine host by unique and rhizobia-like mechanisms boosted by surface-fixed methanol - Koskimäki, Janne J; Pohjanen, Johanna; Ihantola, Emmi-Leena; Sutela, Suvi; Pirttilä, Anna Maria (Oxford University Press, 2026)
Methylorubrum extorquens DSM13060 (Rhizobiales) has a specific capacity to live inside cells of bud meristems in pine trees. The bud niche is almost completely unstudied, although likely widespread in plants. It is unknown how theendosymbioticmethylotrophenterssuchcrucialtissues of the plant. We hypothesized the bud colonization to occur mainly through the shoot epidermis enabled by host-produced methanol. We combined several microscopic methods to illustrate spatio-temporal colonization dynamics and methanol utilization by M. extorquens DSM13060 during the interaction. Our results showed that the endosymbiont mainly enters pine seedlings through cylindrical sheath,whichisalayeroflivingcellssurrounding primary root and transition zone. The cylindrical sheath played a central role in accumulation and proliferation of bacteria before entering deeper tissues. The endosymbiont also penetrated host through epidermis and stomatal apertures in stem and formed infection pocket-like structures upon entry. M. extorquens DSM13060 activated the mxaFpromoter on plant surfaces for methanol assimilation prior to shifting to the endosymbiotic lifestyle. Our results suggest that the surface-bound methanol was used for production of antioxidants that enable tissue penetration, documented earlier. Gradual cell-to-cell passage or formation of intracellular infection threads enabled the invasion past endodermis into the xylem. The xylem was observed to function as the main route to the apical meristem, where bacteria were present after 90 days of inoculation. Our study widens the previously known niches and reveals unique and rhizobia-like colonization mechanisms by the endosymbiont in the above and belowground parts of pine.
Keywords: Methylorubrum; endophyte; endosymbiont; plant-microbe interaction; methanol utilization; MxaF